Hydrophilicity-Hydrophobicity Transformation, Thermoresponsive Morphomechanics, and Crack Multifurcation Revealed by AIEgens in Mechanically Strong Hydrogels - Hu, Yubing (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 Wiley-VCH GmbH.